Predictive factors for time to recurrence, treatment and post-recurrence survival in patients with initially resected colorectal liver metastases. Issue 1 (December 2015) - Angelsen, Jon-Helge; Viste, Asgaut; Løes, Inger; Eide, Geir; Hoem, Dag; Sorbye, Halfdan; Horn, Arild
Abstract Background Despite progress in resection for colorectal liver metastases (CLM), the majority of patients experience recurrence. We aimed to evaluate factors influencing time to recurrence (TTR), treatment and post-recurrence survival (PRS) related to site of recurrence. Methods This is a retrospective population-based cohort study (1998–2012) of consecutive patients without extrahepatic disease treated with resection for CLM in a referral centre. Results A total of 311 patients underwent resection for CLM. After a median follow-up of 4.2 years (range 1.2–15.2), 209 (67.4 %) patients developed recurrence, hepatic 90, extrahepatic 59 and both 60. Median TTR was 14.0 months, and 5-year recurrence-free status was 25.7 %. Five- and 10-year overall survival (OS) was 38.8 and 22.0 %, respectively. Median OS was 45 months. A multivariate analysis displayed synchronous disease (hazard ratio (HR) 1.50), American Society of Anaesthesiologists (ASA) score (HR 1.40), increasing number (HR 1.24) and size of metastases (HR 1.08) to shorten TTR (allp < 0.05). Perioperative chemotherapy (n = 59) increased overall TTR (HR 0.63) and overall survival (OS; HR 0.55). Hepatic TTR was correlated to synchronous disease (HR 2.07), number of lesions (HR 1.20), R1 resection (HR 2.00) and ASA score (HR 1.69), whereas extrahepatic TTR was correlated to N stage of the primary (HR 1.79), number (HR 1.27) and size of metastases (HR 1.16). Single-site recurrence was most common (135 of 209, 64.5 %), while 58 patients had double- and 16 triple-site relapses. Median PRS was 24.3 months. There was a difference in median PRS (months) according to site of relapse: liver 30.5, lung 32.3, abdominal 22.0, liver and lung 14.3, others 14.8 (p = 0.002). Repeated liver resections were performed inn = 57 patients resulting in 40.6 months median OS and 36.8 % 5-year OS. Conclusions An adverse overall TTR was correlated to number and size of metastases, ASA score and synchronous disease. Perioperative chemotherapy increased TTR and OS after surgery for CLM. Patients with solitary post-resection relapse in the liver or lungs had the potential for longevity due to multimodal treatment.